PEMANFAATAN BIJI KARET SEBAGAI AGREGAT KASAR TERHADAP WORKABILITY DAN KUAT TEKAN BETON SCC (SELF COMPACTING CONCRETE) - Vike Itteridi; Suci Damaiati; Heri Wijaya (JURNAL ILMIAH BERING'S, 2022)
Self compacting concrete is that can utilize its own weight to be able to flow to fill the room without any compaction process at all. The purpose of this study was to determine the compressive strength of self-compacting concrete with the substitution of rubber seeds as coarse aggregate. The method used in this study is an experimental method (experimental), also discusses the distribution of Slump Flow with the use of rubber seeds, the rate of use of rubber seeds is 3%, 4% and 5% of the weight of the coarse aggregate (split) used. The results of this study indicate the optimum compressive strength at the age of 28 days of concrete with the highest value in code A which is 8.93 MPa with a specific gravity of 2.33 grams/cm³ and a Slump Flow value of 52 cm. From this research, it can be concluded that the less mixing of rubber seeds in concrete composition the higher the compressive strength and the lower the specific gravity, while the Slump Flow value obtained will be lower. Due to the brittle nature of the rubber seeds, the slippery surface of the rubber seeds and the lightweight rubber seeds.